Experimental determination of HSS model parameters for typical Zhengzhou strata and their application in shield tunnel construction - Pi, Jingkun; Xu, Yumin; Zhang, Jingyao; Du, Zibo; Zeng, Yingjun (Frontiers in Earth Science, 2025)
The hardening small strain (HSS) model can accurately capture the stress-related characteristics of soil during the small strain stage. This model has been widely used in calculating deformations for tunnels and excavations in sand and clay strata. However, research on the appropriate parameter values for silt remains insufficient. In this research, a series of laboratory tests were conducted to determine the parameters for the HSS model for strata typical of Zhengzhou. Subsequently, a three-dimensional finite-element model was established based on the newly constructed Zhengzhou Metro Line eight shield overpass the existing Line two to simulate the case of shield tunnel construction closely passing over an existing tunnel. To verify the applicability and accuracy of the HSS model, the simulation results were compared with actual measurement data. Based on the numerical simulation, a further analysis was conducted on surface settlement, stratified settlement of the strata, and the deformation of the existing tunnel during the construction. The results obtained using the HSS model were compared with the measured values, showing good agreement. This indicates that the HSS model is capable of effectively predicting deformation. The simulation results indicate that during the construction process, the strata first experienced settlement and then uplift. When the shield tail reached the monitoring section, the settlement of each stratum reached its maximum value. As the shield tail passed through the monitoring section, each stratum experienced a noticeable uplift. Additionally, the existing tunnel was primarily uplifted after the shield tail passed beyond it. Notably, the uplifting range and amount were greater at the tunnel’s vault compared to the arch bottom. These findings provide a valuable reference for related shield passage projects in the Zhengzhou area and demonstrate the value of the HSS model parameters.